Battery and membrane electrode assembly
By introducing reinforcing materials into or between layers of the battery and membrane electrode joint, the problem of insufficient durability of the existing battery and membrane electrode joint is solved, and higher mechanical strength and durability are achieved.
Patent Information
- Application Number
- CN202080058552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-19
- Filing Date
- 2020-08-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-08-14
AI Technical Summary
The existing battery and membrane electrode joints are prone to skew, deformation and damage when temperature, humidity and pressure change, resulting in insufficient durability.
Reinforcing materials are introduced into or between the layers of the battery and membrane electrode joint to improve mechanical strength. The reinforcing material can be mixed or impregnated with the layers of the electrode and the electrolyte membrane to form a polymer electrolyte membrane with high structural regularity.
By introducing reinforcement materials, the durability of the battery and membrane electrode joint is significantly improved, which can withstand expansion and contraction caused by changes in temperature, humidity and pressure, and reduce damage and deformation.
Smart Images

Figure 199501 
Figure 223126 
Figure 133171DEST_PATH_IMAGE010
Abstract
Description
Technical Field
[0001] The present invention relates to a battery and a membrane electrode assembly. Background Art
[0002] In the past, chemical batteries such as lithium-ion batteries and solid polymer fuel cells (PEFC) were used as batteries to supply power to vehicles. Chemical batteries usually have a stacked structure. For example, PEFC is a stacked body with an insulator stacked on a membrane electrode assembly, and the membrane electrode assembly is also a stacked body with a solid polymer electrolyte membrane between a pair of electrodes. Most electrodes are also composed of multiple layers such as a catalyst layer and a gas diffusion layer.
[0003] The electrolyte membrane is expected to be thinner in order to reduce the resistance, but if it is too thin, pinholes and cracks may occur. Therefore, research and development of electrolyte membranes with excellent mechanical strength are underway (for example, see Patent Documents 1 and 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2010 / 044436
[0007] Patent document 2: Japanese Patent Application Publication No. 2011-21176. Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, if the overall durability of a battery having a laminated structure is to be improved, it is not only the electrolyte membrane that is expected to have mechanical strength. In particular, the environmental conditions of the battery installed in the vehicle are prone to change, and high durability is required. For example, heating and cooling cycles are repeated according to temperature changes, and wetting and drying cycles are repeated according to humidity changes. In addition, due to changes in atmospheric pressure, impacts during driving, etc., cycles of pressurization and decompression of each layer are repeated.
[0010] During this period, the layers of the battery repeatedly expand and contract, sometimes causing damage such as cracks. In addition, due to the differences in the thermal expansion coefficients, tensile strength and other physical properties of the materials used in the layers of the battery, sometimes the battery may become distorted, deformed, stretched by adjacent layers, etc., causing damage. In addition, damage may also occur due to mixed impurities and penetration of fibrous substances.
[0011] An object of the present invention is to provide a battery or a membrane electrode assembly having high durability.
[0012] Means for solving problems
[0013] According to one aspect of the present invention, a battery (100) is provided, which is a multilayer structured battery (100) including a pair of electrode (1) layers, wherein the battery (100) has a reinforcing material (20) disposed in one or more layers or between layers.
[0014] According to one aspect of the present invention, a membrane electrode assembly (3) is provided, which comprises a pair of electrodes (1) and an electrolyte membrane (2) between the pair of electrodes (1), wherein the electrodes (1) have a multilayer structure, and the membrane electrode assembly (3) has a reinforcing material (20) arranged in one or more layers or between layers of the electrodes (1) and the electrolyte membrane (2).
[0015] Effects of the Invention
[0016] According to the present invention, a battery or a membrane electrode assembly having high durability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a cross-sectional view showing the structure of a polymer electrolyte fuel cell according to this embodiment.
[0018] Figure 2 This is a cross-sectional view showing an example of a damaged portion in a polymer electrolyte fuel cell. DETAILED DESCRIPTION
[0019] Hereinafter, embodiments of the battery and the membrane electrode assembly of the present invention will be described with reference to the drawings. The configuration described below is an example (representative example) of one embodiment of the present invention, and the present invention is not limited to the configuration described below.
[0020] The battery of the present invention is a chemical battery or a physical battery comprising a pair of electrodes, and has a multilayer structure in which a plurality of layers comprising electrodes are stacked. Examples of chemical batteries include alkaline manganese batteries, nickel-hydrogen batteries, lithium-ion secondary batteries, fuel cells, and the like, and examples of physical batteries include solar cells, etc.
[0021] Hereinafter, a polymer electrolyte fuel cell (PEFC) will be described as one embodiment of the battery of the present invention. However, the present invention can be applied to any battery having a multilayer structure including a pair of electrodes as described above, similarly to the PEFC.
[0022] (PEFC)
[0023] Figure 1 The configuration of PEFC 100 as one embodiment of the present invention is shown.
[0024] like Figure 1 As shown, the PEFC 100 includes a membrane electrode assembly (MEA) 3 and two separators 4 provided on both sides of the MEA 3 .
[0025] (MEA)
[0026] The MEA 3 includes a pair of electrodes 1 and an electrolyte membrane 2 provided between the pair of electrodes 1 .
[0027] (electrode)
[0028] One electrode 1 of the pair is an anode, also called a fuel electrode. The other electrode 1 is a cathode, also called an air electrode. At the anode, hydrogen (H2) supplied through the separator 4 generates electrons (e - ) and protons (H + ) reaction. Electrons move to the cathode via the external circuit. The movement of electrons generates current in the external circuit. Protons move to the cathode via the electrolyte membrane 2. At the cathode, oxygen (O2) is supplied through the separator 3, and oxygen ions (O2) are generated by the electrons moving from the external circuit. - The oxygen ions and the protons (2H + ) combine to form water (H2O).
[0029] The electrode 1 has at least a catalyst layer 11. The electrode 1 may have a multilayer structure, and may have a gas diffusion layer 12 and a porous layer 13, for example, in order to improve gas diffusibility.
[0030] The catalyst layer 11 promotes the reaction of hydrogen and oxygen using a catalyst. The catalyst layer 11 includes a catalyst, a carrier that supports the catalyst, and an ionomer that covers the catalyst.
[0031] Examples of the catalyst include metals such as platinum (Pt), ruthenium (Ru), iridium (Ir), rhodium (Rh), palladium (Pd), and tungsten (W), and mixtures and alloys thereof. Among them, platinum, mixtures and alloys containing platinum are preferred from the viewpoints of catalyst activity, resistance to poisoning by carbon monoxide, and heat resistance.
[0032] Examples of the support include porous metal compounds having fine pores such as mesoporous carbon and Pt black. Mesoporous carbon is preferred because it has good dispersibility, a large surface area, and little particle growth at high temperatures even when a large amount of catalyst is supported.
[0033] As the ionomer, an ion-conductive polymer electrolyte similar to the electrolyte membrane 2 described later can be used.
[0034] The gas diffusion layer 12 can evenly diffuse the gas supplied through the separator 4 to the catalyst layer 11. As the gas diffusion layer 12, for example, a porous fiber sheet having conductivity, gas permeability and gas diffusivity such as carbon fiber, or a metal plate such as foamed metal or expanded metal can be used.
[0035] The porous layer 13 is provided as an intermediate layer between the catalyst layer 11 and the gas diffusion layer 12, which can reduce the resistance of the electrode 1 and improve the flow of the gas. In addition, the porous layer 13 can promote the discharge of water generated in the electrolyte membrane 2 and inhibit back diffusion. As the porous layer 13, for example, a porous sheet made by mixing conductive carbon with a water-repellent binder resin can be cited. From the perspective of water transportability, a porous body with an average pore size of 1 to 10 nm is preferred. As carbon, for example, graphite, carbon black, graphene, carbon nanotubes, carbon fibers, etc. can be used.
[0036] (Electrolyte membrane)
[0037] The electrolyte membrane 2 is an ion-conductive polymer electrolyte membrane. Examples of the electrolyte membrane 2 include perfluorosulfonic acid polymers such as Nafion (registered trademark) and Aquavio (registered trademark); aromatic polymers such as sulfonated polyetheretherketone (SPEEK) and sulfonated polyimide; and aliphatic polymers such as polyvinylsulfonic acid and polyvinylphosphoric acid.
[0038] From the viewpoint of improving durability, electrolyte membrane 2 can be a composite membrane formed by infiltration of polymer electrolyte in porous substrate 2a. As porous substrate 2a, as long as it is capable of carrying polymer electrolyte, it is not particularly limited, and films such as porous, fabric-like, nonwoven-like, fibrillar, etc. can be used. The material of porous substrate 2a is not particularly limited either, but from the viewpoint of improving ion conductivity, it is possible to use such polymer electrolyte as described above. Among them, the strength and shape stability of polytetrafluoroethylene, polytetrafluoroethylene-chlorotrifluoroethylene copolymer, polychlorotrifluoroethylene, etc. as fluorine-based polymers are excellent.
[0039] (Isolator)
[0040] The separator 4 is a plate having ribs 4b on the surface for forming a gas flow path 4a, and is also called a bipolar plate. As a material for the separator 4, metal is generally used. For example, carbon is used from the viewpoint of lightness, and stainless steel is used from the viewpoint of thickness reduction.
[0041] (Reinforcement material)
[0042] The PEFC 100 includes a reinforcing material 20 having excellent mechanical strength within one or more layers including the electrode 1 or between layers.
[0043] If environmental conditions such as temperature, humidity, and pressure change and cycles of heating and cooling, wetting and drying, pressurization and decompression are repeated, loads such as distortion and deformation of each layer constituting the PEFC 100 and tensile force between each layer may be generated. Even if such loads are generated, the reinforcement material 20 can alleviate the loads and reduce the damage to each layer.
[0044] Figure 2 An example of a damaged portion of PEFC 100 is shown by triangular marks P1 to P7 .
[0045] If the above-mentioned cycles of heating and cooling, wetting and drying, pressurization and decompression are repeated, the catalyst layer 11, gas diffusion layer 12, porous layer 13, electrolyte membrane 2 and separator 4 constituting the electrode 1 may be distorted or deformed, and cracks or other damage may occur inside the layers indicated by marks P1 to P5. In addition, due to the difference in physical properties such as thermal expansion coefficient and tensile strength between each layer and the adjacent layer, each layer is stretched by the adjacent layer, and damage may sometimes occur inside the layers indicated by marks P1 to P5.
[0046] The electrolyte membrane 2 is prone to internal damage as shown by the mark P1 due to repeated cycles of swelling during operation and shrinking during stop. When the electrolyte membrane 2 expands, due to the difference in properties with the adjacent catalyst layer 11, damage may sometimes occur at the boundary between the catalyst layer 11 and the electrolyte membrane 2 protruding from the catalyst layer 11, that is, at the position shown by the mark P7.
[0047] In addition, when an impact is applied from the outside, a load is applied to the contact portion between the ribs 4b on the surface of the insulator 4 and the gas diffusion layer 12, especially the portion in contact with the corners of the ribs 4b, and sometimes the gas diffusion layer 12 is destroyed at the positions indicated by marks P5 and P6.
[0048] By appropriately using the reinforcing material 20 at the damaged portions indicated by the marks P1 to P7, the damage of each layer can be reduced. Figure 2 The positions indicated by the marks P1 to P7 in FIG. 1 are examples of the destroyed parts, and are not limited to these.
[0049] The reinforcing material 20 disposed in each layer can be mixed with the components of the catalyst layer 11, the gas diffusion layer 12, the porous layer 13 and each layer of the electrolyte membrane 2 of the electrode 1 to form each layer, or can be impregnated in each layer. For example, the electrolyte membrane 2 can be formed by mixing a polymer electrolyte with the reinforcing material 20 and forming a film. In addition, the porous substrate 2a of the electrolyte membrane 2 can be constituted by the reinforcing material 20, or the reinforcing material 20 can be impregnated in the substrate 2a. In addition, the catalyst layer 11, the gas diffusion layer 12 or the porous layer 13 can be impregnated in the liquid tank of the reinforcing material 20, or the reinforcing material 20 can be impregnated in the porous material of each layer.
[0050] The reinforcing material 20 disposed between each layer can be a sheet with a gap, or can be a coating covering the surface of each layer. As long as it is such a reinforcing material 20, the reduction of conductivity can be prevented. The shape of the sheet with a gap is not particularly limited, and porous, mesh, fabric, nonwoven, fibril, etc. can be cited. The sheet can be pasted to each layer using an adhesive. The coating of the reinforcing material 20 can be provided by, for example, impregnating or coating the reinforcing material 20 on the surface of at least one of the layers on both sides. When the coating is thin, for example, the coated layer is porous, the porous shape can remain unchanged.
[0051] The mechanical strength of the reinforcing material 20 can be improved by designing a polymer with high structural regularity. For example, the mechanical strength of the reinforcing material 20 can be improved by designing in a manner that increases crystallinity, such as by increasing the cis configuration, sharpening the molecular weight distribution of the polymer chain, increasing the regular folding structure, and extending the polymer chain.
[0052] Although the reinforcing material 20 may or may not have ion conductivity, the reinforcing material 20 having ion conductivity may be used as, for example, the ionomer of the catalyst layer 11, or part or all of the polymer electrolyte of the electrolyte membrane 2. In addition, the reinforcing material 20 having ion conductivity can impart hydrophilicity. Therefore, from the viewpoint of imparting ion exchange function, or imparting hydrophilicity to improve the water discharge or wettability of the layer where the reinforcing material 20 exists, the reinforcing material 20 preferably has an ion exchange group and has ion conductivity.
[0053] The reinforcing material 20 can be disposed in the layer or between the layers on either the anode side or the cathode side, or in the layer or between the layers on both sides, but the reinforcing material 20 disposed on the anode side preferably has an ion exchange group and has ion conductivity. The ion conductivity of the anode side is easily reduced due to drying, but the reinforcing material 20 can make up for the ion conductivity of each layer.
[0054] In the PEFC 100 of this embodiment, a reinforcing material 20 as a mesh sheet is provided between the gas diffusion layer 12 on the anode side and the separator 4, and between the gas diffusion layer 12 on the cathode side and the separator 4. In addition, the reinforcing material 20 having ion conductivity is impregnated into the porous layer 13 on the anode side.
[0055] The ion conductivity of the reinforcing material 20 may have a gradient depending on the positional relationship between the electrolyte membrane 2 and the reinforcing material 20. For example, the ion conductivity of the reinforcing material 20 is preferably higher as the position of the reinforcing material 20 is closer to the electrolyte membrane 2. The higher the ion conductivity of the reinforcing material 20, the easier it is for protons generated at the anode to move to the cathode, and the easier it is for the power generation efficiency to be improved.
[0056] The ion conductivity of the reinforcing material 20 can be measured based on a film formed of the reinforcing material 20 in accordance with JIS R 1661:2004.
[0057] As a specific example of the reinforcing material 20 with ion conductivity, a high cis-diene polymer having a cis-1,4 bond content of 85% or more and an ion exchange group, a stretched polytetrafluoroethylene (PTFE) film described in International Publication 2010 / 044436, a polyurea electrolyte described in Japanese Patent Publication No. 2011-21176, etc. can be cited, but as long as it is a material with excellent mechanical strength, it is not limited to this. One of them can be used alone or in combination of two or more as a reinforcing material 20. In addition, as a reinforcing material 20, a commercial product can also be used. As a commercial product, for example, PrimoSpire (registered trademark) (self-reinforced polyphenyl, Solvay Company), Kapton (registered trademark) (heat-resistant and cold-resistant polyimide film, DuPont Company) and the like can be cited.
[0058] <High cis-diene polymer>
[0059] Among them, high cis-1,4-bond content of 85% or more is preferred in terms of high tensile strength and excellent durability. Generally, diene polymers have cis-1,4 bonds, trans-1,4 bonds and trans-1,2 bonds between monomer units, but from the viewpoint of improving elongation crystallinity and further mechanical strength, the cis-1,4-bond content of the high cis-diene polymer used in the present invention is preferably 90% or more, more preferably 95% or more, further preferably 97% or more, and particularly preferably 99% or more.
[0060] The cis-1,4 bond amount can be measured by Fourier transform infrared spectroscopy (FT-IR).
[0061] The molecular weight of the high cis-diene polymer is not particularly limited, but if it is used as a polymer electrolyte membrane, it is preferably 1,000 or more, more preferably 10,000 or more, and particularly preferably 100,000 or more, expressed as a number average molecular weight converted to polystyrene. As long as it is above the above lower limit, sufficient mechanical strength is easily obtained. In addition, if it is used as a polymer electrolyte in a catalyst layer for fuel cells, it is preferably 5,000,000 or less, more preferably 1,000,000 or less, and particularly preferably 500,000 or less. As long as it is below the above upper limit, sufficient oxygen permeability and ion conductivity are easily obtained, and in addition, solubility when preparing ink for the catalyst layer is also easily obtained. The number average molecular weight can be calculated by gel permeation chromatography (GPC).
[0062] The electrolyte membrane 2 containing the high cis-diene polymer has excellent mechanical durability and can withstand long-term continuous use even if the membrane thickness is reduced. Therefore, compared with conventional polymer electrolytes, the high cis-diene polymer can be suitably used for PEFC applications even if the ion exchange capacity (IEC: Ion Exchange Capacity) is relatively small.
[0063] From the viewpoint of improving ion conductivity, the IEC of the high cis diene polymer is preferably 0.1 meq / g or more, more preferably 0.5 meq / g or more, and further preferably 1.0 meq / g or more. In addition, from the viewpoint of dimensional stability during water absorption, the IEC of the high cis diene polymer is preferably 3 meq / g or less, more preferably 2.5 meq / g or less, and further preferably 2 meq / g or less. Therefore, the IEC of the high cis diene polymer is preferably 0.1 to 3 meq / g, more preferably 0.5 to 2.5 meq / g, and further preferably 1.0 to 2 meq / g.
[0064] The high cis-diene polymer having a cis-1,4 bond content of 85% or more and having an ion exchange group is a copolymer including a high cis-diene polymer component and a polymer component having an ion exchange group.
[0065] Examples of copolymers of a high cis-diene polymer component and a polymer component having an ion exchange group include graft copolymers, statistical copolymers, block copolymers, and combinations thereof. Examples of block copolymers include diblock copolymers, triblock copolymers, and multiblock copolymers.
[0066] The ratio of the content of the polymer component having an ion exchange group to the content of the high cis-diene polymer component [(content of the high cis-diene polymer component) / (content of the polymer component having an ion exchange group)] can be any ratio as long as it is within the range of the above IEC. That is, the ratio can be appropriately adjusted within the range of the above IEC according to the purpose. For example, from the viewpoint of further improving the mechanical strength, the ratio of the high cis-diene polymer component can be increased, and from the viewpoint of improving the ion conductivity, the ratio of the polymer component having an ion exchange group can be increased.
[0067] <High cis-diene polymer component>
[0068] The high-cis diene polymer component undergoes elongation and crystallization, thereby imparting excellent mechanical strength such as tensile strength and abrasion resistance to the reinforcing material 20 .
[0069] From the viewpoint of improving mechanical strength, the high cis-diene polymer component is preferably a conjugated diene having 4 to 12 carbon atoms. Examples of the conjugated diene having 4 to 12 carbon atoms include 1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 4-methyl-1,3-pentadiene, 2,4-hexadiene, etc. These can be used alone or in combination of two or more. Among them, 1,3-butadiene or 2-methyl-1,3-butadiene is preferred, and 1,3-butadiene is more preferred.
[0070] As a high cis-diene polymer component, in addition to the above-mentioned conjugated diene, other components that can form a copolymer with the conjugated diene may also be included. As other components, from the viewpoint of improving heat resistance, reducing the proportion of double bonds in the main chain of the copolymer, and increasing the design freedom as an elastomer by reducing crystallinity, it is preferred to include non-conjugated olefins. Non-conjugated olefins are preferably non-cyclic olefins and have 2 to 10 carbon atoms. As such non-conjugated olefins, α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene are preferred. α-olefins have double bonds at the α position of the olefin, so they can be efficiently copolymerized with conjugated dienes. Among the above-mentioned α-olefins, ethylene, propylene or 1-butene are more preferred, and ethylene is further preferred. These non-conjugated olefins can be used alone or in combination of two or more.
[0071] In addition to the above-mentioned non-conjugated olefins, other components capable of forming a copolymer with the conjugated diene include, for example, styrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, 2,4-dimethylstyrene, ethylstyrene, p-tert-butylstyrene, α-methylstyrene, α-methyl-p-methylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, p-bromostyrene, 2-methyl-1,4-dichlorostyrene, 2,4-dibromostyrene, aromatic vinyls such as vinylnaphthalene, cyclic olefins such as cyclopentene, dicyclopentadiene, 2-norbornene, and 5-ethylidene-2-norbornene, non-conjugated dienes such as 1,5-hexadiene, 1,6-heptadiene, and 1,7-octadiene, methyl (meth)acrylate, (meth)acrylonitrile, and (meth)acrylamide.
[0072] Examples of the high cis-diene polymer component obtained as a result of the polymerization include butadiene polymers and butadiene-ethylene copolymers.
[0073] <Polymer component having ion exchange groups>
[0074] The polymer component having an ion exchange group imparts ion conductivity to the reinforcing material 20 .
[0075] The ion exchange group is not particularly limited, and may be an anionic group or a cationic group.
[0076] Examples of the anionic group include sulfonic acid groups, phosphoric acid groups, carboxylic acid groups, boric acid groups, and sulfonimide groups. Among them, sulfonic acid groups are preferred from the perspective of excellent ion conductivity. The counter cation is not particularly limited, but is preferably an alkali metal ion, H + , monovalent cations such as quaternary ammonium ions.
[0077] Examples of the cationic group include unsubstituted amino, N-alkylamino, N-dialkylamino and other amino groups, pyridyl, imidazolyl and other nitrogen-containing heterocyclic rings, N-trialkylammonium, N-alkylpyridinium, N-alkylimidazolyl, thiourea, isothiouronium and other quaternary ammonium groups. The counter anion of the quaternary ammonium group is not particularly limited, but is preferably PF6 - 、SbF6 - 、AsF6 - Halide anions of group 5B elements, BF4 - Halide anions of group 3B elements, I - (I3 - )、Br - , Cl - Halogen anions, ClO4 - Halogen acid anions, AlCl4 - 、FeCl4 - 、SnCl5 - Metal halide anions, such as NO3 - The nitrate anion, p-toluenesulfonate anion, naphthalenesulfonate anion, CH3SO3 - CF3SO3 - Organic sulfonic acid anions, CF3COO - 、C6H5COO - Carboxylic acid anions, OH - Equivalent anion.
[0078] The polymer component into which the ion exchange group is introduced is not particularly limited as long as it is a compound into which the ion exchange group can be introduced and which can form a copolymer with the high cis-diene polymer component. Examples thereof include conjugated dienes such as 1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 4-methyl-1,3-pentadiene, and 2,4-hexadiene, olefins such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and 1-decene, styrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, 2,4-dimethylstyrene, Ethyl styrene, p-tert-butyl styrene, α-methyl styrene, α-methyl-p-methyl styrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, p-bromostyrene, 2-methyl-1,4-dichlorostyrene, 2,4-dibromostyrene, aromatic vinyls such as vinylnaphthalene, cyclopentene, dicyclopentadiene, 2-norbornene, 5-ethylidene-2-norbornene and other cyclic olefins, 1,5-hexadiene, 1,6-heptadiene, 1,7-octadiene and other non-conjugated dienes, methyl (meth)acrylate, (meth)acrylonitrile, (meth)acrylamide, etc.
[0079] Although exemplary compounds (1) to (4) of the polymer component having an ion exchange group are shown below, the present invention is not limited thereto.
[0080] [Chemistry 1]
[0081]
[0082] In the formula, M is a hydrogen atom or an alkali metal atom.
[0083] [Chemistry 2]
[0084]
[0085] In the formula, M is a hydrogen atom or an alkali metal atom.
[0086] [Chemistry 3]
[0087]
[0088] In the formula, M is a hydrogen atom or an alkali metal atom.
[0089] [Chemistry 4]
[0090]
[0091] In the formula, M is a hydrogen atom or an alkali metal atom.
[0092] As the polymer having an ion exchange group obtained as a result of polymerization, for example, a fluorine-based polymer having an ion exchange group, an aliphatic polymer having an ion exchange group, and an aromatic polymer having an ion exchange group can be cited. In other words, the polymer component having an ion exchange group also includes monomers constituting the polymer with these polymers.
[0093] As fluorine-based polymers containing ion exchange groups, for example, perfluorosulfonic acid polymers can be cited. Perfluorosulfonic acid polymers have polytetrafluoroethylene (PTFE) units and perfluorosulfonic acid units. As perfluorosulfonic acid polymers, commercial products can also be used. As commercial products that can be used, for example, Nafion (Nafion: registered trademark, manufactured by DuPont), Aquivion (Aquivion: registered trademark, manufactured by Solvay), Flemion (Flemion: registered trademark, manufactured by Asahi Glass Co., Ltd.), Aciplex (Aciplex: registered trademark, manufactured by Asahi Kasei Corporation) and the like can be cited.
[0094] Exemplary compounds (5) to (7) of perfluorosulfonic acid polymers are shown below, but are not limited thereto. Exemplary compounds (5) and (6) are Nafion (registered trademark) and Aquavio (registered trademark), respectively. Exemplary compound (7) is an ionomer proposed by 3M Company.
[0095] [Chemistry 5]
[0096]
[0097] In the formula, n is an integer greater than or equal to 1.
[0098] [Chemistry 6]
[0099]
[0100] In the formula, n is an integer greater than or equal to 1.
[0101] [Chemistry 7]
[0102]
[0103] In the formula, n is an integer greater than or equal to 1.
[0104] Examples of the aliphatic polymer having an ion exchange group include polyvinylsulfonic acid and polyvinylphosphoric acid.
[0105] Examples of the aromatic polymer having an ion exchange group include sulfonated polyetheretherketone (SPEEK), sulfonated polyethersulfone (SPES), sulfonated polyphenylsulfone (SPPSU), sulfonated polyimide, sulfonated polyetherimide, sulfonated polysulfone, and sulfonated polystyrene.
[0106] Although exemplary compounds (8) to (10) of the aromatic polymer containing an ion exchange group are shown below, the present invention is not limited thereto.
[0107] The exemplary compound (8) is SPEEK, the exemplary compound (9) is SPES, and the exemplary compound (10) is sulfonated polyetherimide.
[0108] [Chemistry 8]
[0109]
[0110] In the formula, n is an integer greater than or equal to 1.
[0111] [Chemistry 9]
[0112]
[0113] In the formula, n is an integer greater than or equal to 1.
[0114] [Chemistry 10]
[0115]
[0116] In the formula, k, m and n are integers greater than 1.
[0117] <Method for producing high-cis diene polymer>
[0118] The high cis-diene polymer can be produced according to the conventionally known method. Usually, it can be obtained by polymerizing each component in the presence of a catalyst such as a Ziegler-Natta catalyst, a nickel catalyst, an aluminum catalyst, a lanthanide catalyst composition catalyst, or a metallocene complex catalyst. Among these catalysts, a lanthanide catalyst composition catalyst or a metallocene complex catalyst is preferably used.
[0119] The lanthanide-based catalyst composition-based catalyst is not particularly limited, and, for example, a known lanthanide-based catalyst composition-based catalyst described in JP-A-2015-508843 or the like can be used.
[0120] The metallocene complex catalyst is not particularly limited, and the known metallocene complex catalysts described in, for example, Japanese Patent Application Laid-Open No. 2012-162627 and Japanese Patent Application Laid-Open No. 2012-180457 can be used. Among the metallocene complex catalysts, a gadolinium metallocene complex catalyst using gadolinium as a lanthanide is more preferably used. The gadolinium metallocene complex catalyst has a very high activity, and thus a high polymer electrolyte with a high cis-1,4 bond amount can be obtained by using the catalyst. In addition, due to the very high activity, the amount of the catalyst used can be greatly reduced.
[0121] In addition, even when a conjugated diene and a non-conjugated olefin are included as high cis-diene polymer components, a lanthanide-based catalyst composition system and a metallocene complex catalyst are preferred, and the gadolinium metallocene complex catalyst is particularly preferred. By using a gadolinium metallocene complex catalyst, a conjugated diene-olefin copolymer can be efficiently synthesized.
[0122] As a polymerization method, any method such as solution polymerization, suspension polymerization, liquid phase bulk polymerization, emulsion polymerization, gas phase polymerization, solid phase polymerization, etc. can be used. In addition, when a solvent is used in the polymerization reaction, the solvent used can be inert in the polymerization reaction, and examples thereof include aprotic polar solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, etc.; chlorine-based solvents such as dichloromethane, chloroform, 1,2-dichloroethane, chlorobenzene, dichlorobenzene, etc.; alcohols such as methanol, ethanol, propanol, etc.; alkylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, etc. They can be used alone or mixed with two or more solvents as needed.
[0123] By using the above method, appropriately adjusting the addition method, heating conditions, etc., a statistical copolymer, a graft copolymer, a block copolymer, and a combination thereof can be produced. The high cis-diene polymer having a cis-1,4 bond content of 85% or more produced by the above method has high tensile strength and excellent mechanical durability.
[0124] From the viewpoint of improving mechanical strength, the high cis-diene polymer can be a crosslinked body. As a crosslinking method, for example, the use of a crosslinking agent, irradiation with energy rays such as electron beams and radiation, etc. can be cited. As a crosslinking method using a crosslinking agent, for example, a method in which a high cis-diene polymer and a crosslinking agent are dissolved in a solvent to obtain a composition, and crosslinking is performed by heating or light irradiation, etc. can be cited. The crosslinking agent is not particularly limited, and a known crosslinking agent can be used.
[0125] <Method for producing MEA>
[0126] MEA 3 can be manufactured, for example, as follows.
[0127] First, a polymer electrolyte is formed into a membrane to form an electrolyte membrane 2, or a polymer electrolyte is impregnated into a porous substrate 2a to obtain an electrolyte membrane 2. A catalyst layer ink containing a catalyst, a carrier and an ionomer is applied to both sides of the electrolyte membrane 2 to form a catalyst layer 11. Next, the porous layer 13 obtained is attached to the anode side by immersing it in a liquid tank of a reinforcing material 20 so that the reinforcing material 20 is impregnated into the layer, and the porous layer 13 not impregnated with the reinforcing material 20 is attached to the cathode side. A gas diffusion layer 12 is further attached to the porous layer 13 to obtain an MEA 3.
[0128] <PEFC production method>
[0129] PEFC 100 can be produced, for example, as follows.
[0130] The reinforcing material 20 as a mesh sheet is bonded to the surface of the gas diffusion layer 12 of the MEA 3 manufactured as described above. The separator 4 is further bonded to obtain the PEFC 100.
[0131] [Example]
[0132] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not limited to these Examples.
[0133] By the above method, a high cis-1,4-bond content of 85% was obtained. The high cis-1,4-bond content of the diene polymer was formed into a mesh sheet and pasted on a Figure 1 The PEFC 100 shown has the same structure as the PEFC gas diffusion layer, and a reinforcing material is provided between the gas diffusion layer and the separator.
[0134] The PEFC with reinforcement material and the PEFC without reinforcement material were kept at -30°C for 1 hour and then kept at 100°C for 1 hour in a constant humidity chamber, and the hot and cold test was repeated. After 5 cycles of hot and cold test, the damage of each layer of PEFC was visually checked. As a result, it was confirmed that the PEFC without reinforcement material was damaged earlier than the one with reinforcement material, and it was confirmed that the PEFC with reinforcement material had high durability.
[0135] In addition, the same test was conducted using a high cis-1,4-bond content of 95% of a high cis-diene polymer. The results showed that the number of cycles until destruction was confirmed was greater than that of a high cis-1,4-bond content of 85%, indicating that the durability was higher.
[0136] As mentioned above, although the preferred embodiments of the present invention have been described, the present invention is not limited to these embodiments, and various modifications and changes can be made within the scope of the gist of the present invention.
[0137] For example, not limited to the above-mentioned PEFC100, lithium ion batteries, solar cells, etc. are also multilayered batteries including a pair of electrode layers. Even for batteries other than PEFC100, according to the present invention, by providing the reinforcing material 20 within or between the layers, the durability of the entire battery as a stack can be improved.
[0138] Explanation of symbols
[0139] 100・・・PEFC, 1・・・Electrode, 3・・・MEA, 11・・・Catalyst layer, 12・・・Gas diffusion layer, 13・・・Porous layer, 4・・・Separator, 20・・・Reinforcement material
Claims
1. A battery (100) having a multilayer structure comprising a pair of electrode (1) layers, wherein: The battery (100) has a reinforcing material (20) disposed in one or more layers or between layers. The reinforcing material (20) comprises a high cis-diene polymer. The high-cis diene polymer has a cis-1,4 bond content of 85% or more.
2. The battery (100) according to claim 1, wherein: The high-cis diene polymer has a cis-1,4 bond content of 95% or more.
3. The battery (100) according to claim 1 or 2, wherein: The reinforcing material (20) disposed in the layer is mixed with the components of the layer to constitute the layer, or is impregnated in the layer.
4. The battery (100) according to claim 1 or 2, wherein: The reinforcing material (20) disposed between the layers is a sheet having voids, or a coating film covering the surface of at least one of the layers on both sides.
5. The battery (100) according to claim 1 or 2, wherein: The battery (100) is a solid polymer fuel cell. An electrolyte membrane (2) is provided between the pair of electrodes (1). There are separators (4) on both sides of the pair of electrodes (1). The electrode (1) comprises a catalyst layer (11) and a gas diffusion layer (12). The reinforcing material (20) is provided in or between one or more layers of the electrolyte membrane (2), the catalyst layer (11) and the gas diffusion layer (12).
6. The battery (100) according to claim 5, wherein: The reinforcing material (20) has an ion exchange group.
7. The battery (100) according to claim 5, wherein: In the pair of electrodes (1), the reinforcing material (20) provided in a layer or between layers on the side of the electrode (1) serving as an anode has an ion exchange group.
8. A membrane electrode assembly (3) comprising an electrolyte membrane (2) between a pair of electrodes (1), wherein: The electrode (1) has a multi-layer structure. The membrane electrode assembly (3) comprises a reinforcing material (20) provided in one or more layers or between layers of the electrode (1) and the electrolyte membrane (2). The reinforcing material (20) comprises a high cis-diene polymer. The high-cis diene polymer has a cis-1,4 bond content of 85% or more.
Citation Information
Patent Citations
Polyurea electrolyte and production method therefor
JP2011021176A
Copolymer, rubber composition, crosslinked rubber composition, and tire
JP2012162627A
Rubber composition, rubber composition for tire side use, crosslinked rubber composition, and tire
JP2012180457A
Method for preparing high-cispolydienes
JP2015508843A
Reinforced electrolyte membrane for fuel cell, membrane-electrode assembly for fuel cell, and solid polymer fuel cell comprising same
WO2010044436A1